Integrasi Aspek Multikultural dalam Pembelajaran Ilmu Pengetahuan Sosial di Sekolah Dasar - Aprilia, Rara Nasywa; Wahyuni, Endang Sry; Sari, Silfiyana; Fauziah, Sobrini; Sholeh, Muhammad; Fhadilla, Zilza; Wasito, Muhamad (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Cultural diversity in Indonesia, including ethnicity, religion, and race, makes it a rich country, but if not managed wisely, it can lead to conflict. Therefore, it is important to teach and appreciate cultural diversity to the younger generation, including through IPS education in elementary schools. The aim of this research is to explore the integration of multicultural aspects in IPS learning in elementary schools by combining theory and comprehensive multicultural education implementation in the elementary school environment. This research method employs qualitative literature research with secondary data from various sources such as books, journals, and documents, using philosophical and pedagogical approaches. The research steps include introduction, body, and conclusion, and utilize relevant literature sources such as academic articles and books. The research findings suggest that multicultural education in Indonesia aims to build an inclusive learning environment that emphasizes values such as respect, honesty, and tolerance in addressing cultural and racial intolerance issues. Through the Social Sciences subject, this education builds the mental resilience of students to manage social conflicts and cultivate individuals who do not prioritize primordialism or ethnocentrism.